NASAL CARRIAGE OF STAPHYLOCOCCUS AUREUS WITH SPECIAL EMPHASIS ON METHICILLINRESISTANT STAPHYLOCOCCUS AUREUS AMONG STUDENTS OF A SOUTH INDIAN MEDICAL COLLEGE - PREVALENCE AND ANTIBIOGRAM PATTERN - M, Radhakrishna; Taneja, Aishwarya; Rao, Pooja (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Objective: There is paucity of information on carriage of Staphylococcus aureus and Methicillin Resistant S.aureus from developing nations including the medical students who could be the potential transmitters. Present study was aimed at establishing the prevalence and antibiogram pattern of S. aureus with special emphasis on MRSA among II year MBBS students of Kasturba Medical College, Mangalore. Methods: A total of 148 students were participated in this study. Swabs taken from both anterior nares were processed, and the growth of S. aureus was confirmed by standard procedure. Further categorization of S. aureus into MRSA was done using cefoxitin disc diffusion method, along with the antibiogram to other common drugs. Results: The number of strains of S. aureus isolated from our 148 participants was 78 with a percentage rate of 52.7. Of the 78 isolates of S. aureus, 9 (11.5%) were MRSA. The overall MRSA carriage rate was 6.1%. Conclusion: The S. aureus and MRSA carriage rates recorded in this study were significantly higher when compared with other reported studies. It was observed that risk factors like use of antibiotics in past 6 months and snoring were found to be statistically significant in nasal carriage status of S. aureus. Out of nine MRSA carriers, six were found to be having the parents who were busy clinicians by occupation and the close contact with them could be the prime factor in the acquisition of MRSA carriage status. Keywords: Staphylococcus aureus, MRSA, Nasal carriage, Medical students.